The middle and later stone age of the Iringa region southern Tanzania: an introduction - Biittner, Katie; Bushozi, Pastory M.; Willoughby, Pamela R. (My University, 2007)
is well known for the richness of its Stone Age past. But what we know about its early history comes from a limited number of northern sites such as Olduvai Gorge, as well as Nasera rockshelter and Mumba Cave near Lake Eyasi. The Iringa Region in the south, however, also contains a long Stone Age record. It begins with the Acheulean at Isimila Korongo and Mgongo, both located just outside of the modern regional capital of Iringa. But the Stone Age past continues in a series of granite rockshelters and caves. Pamela Willoughby first saw these sites in 2005, and directed brief test excavations of two of them in 2006. It became clear immediately that they may contain the entire post-Acheulean cultural record. This paper introduces three rockshelters from which archaeological material was recovered in July and August 2006. This research was done to test models of the emergence of modern humans in this part of Africa (Willoughby 2007). This article introduces new sites and presents preliminary results from the initial fieldwork. Pamela Willoughby describes the sites, the general framework of this research project, and the cultural history of Iringa. Her two PhD students, Katie Biittner and Pastory Bushozi, discuss their own research.
Keywords: Stone Age; Tanzania; Iringa region; modern humans